Strategi Dinas Lingkungan Hidup dan Kebersihan dalam Pengelolaan Sampah pada Kawasan Pantai Kabupaten Pangandaran - Arif Nailda Amali; Otong Husni Taufiq; Ii Sujai (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This research is based on problems in the strategy of the environment and hygiene agency in waste management in the coastal area of Pangandaran Regency, including: 1). There are limitations of supporting facilities and infrastructure in waste management in coastal areas. 2). Low sense of responsibility and participation of the community and tourists in protecting the coastal environment from garbage. 3). A directed and sustainable waste management strategy in coastal areas has not been prepared by the Pangandaran Regency Environment and Hygiene Office. The purpose of this study is to find out the strategy of the environment and hygiene agency in waste management in the coastal area of Pangandaran Regency. The method used in this study is a descriptive method with a qualitative research approach. This study uses Primary Data and Secondary Data. The primary data in this study is the result of interviews with 8 informants consisting of 1 head of service, 1 head of field, 2 cleaners, and 4 community leaders from coastal areas. Secondary data in this study are documents that have relevance to the research. The data collection technique in this study consists of interviews, observations and documentation. The data analysis techniques in this study consist of data reduction, data display and conclusion or verification. The results of the study show that the strategy of the environment and hygiene agency in waste management in the coastal area of Pangandaran Regency has not run optimally. The obstacles are due to the ineffectiveness of the recycling program, the lack of public awareness, the absence of the application of technology and management strategies that have not involved the participation of other stakeholders, and the weak role of coordination among stakeholders. DLHK's efforts to overcome obstacles by education, policy issuance, and provision of basic waste management facilities.